Drama and Intelligence: A Cognitive Theory - Courtney, Richard (MQUP, 1990)
Drama, as defined by Courtney, encompasses all kinds of dramatic action, from children's play to social roles and theatre. He shows not only that teachers have found educational drama and spontaneous improvisation to be an invaluable learning tool but that many skills required for work and leisure reflect the theatrical ability to "read" others and see things from their point of view.